Molecular Mechanisms of the Aging Process and Rejuvenation - Shiomi, Naofumi (IntechOpen, 2016)
Numerous studies had been performed to elucidate the mechanisms of aging and to achieve rejuvenation, with some success reported in recent years. However, at present, the findings from those studies are not sufficient to resolve the issue of aging. This book presents an overview of recent topics on cellular aging and rejuvenation. In the early chapters, the molecular mechanisms of aging via the activities of clock and ion channel proteins, in addition to overall aspects, are discussed. In the latter part, the aging of the skin, immune system, and brain is discussed. This book will prove useful for those studying or developing new drugs to counter the aging process and will encourage the development of novel ideas for rejuvenation.